Clinical determinants of physical activity and sedentary behaviour in individuals with schizophrenia - Nur Amirah Abdul Rashid (2021)
Modifiable lifestyle factors such as physical activity (PA) have ameliorative effects on commonly reported health conditions in schizophrenia like cardiovascular diseases and diabetes. Similarly, reduction in sedentary behaviour (SB) promotes better physical health. However, engaging individuals with schizophrenia in PA and less SB can be challenging because of symptoms of schizophrenia. The aims of the present study are (i) to examine the profiles of PA and SB in individuals with schizophrenia; and (ii) to identify their respective clinical determinants.